The experience of the Cultural Action of the Hip-Hop Movement under the viaduct of Madureira in Rio de Janeiro - Takaki, Emika; Coelho, Glauci (Risco - Journal of Architecture and Urbanism, 2008)
We try to give visibility to the Hip-Hop Movement as cultural action capable of enhancing the revitalization of residual public spaces in contemporary cities. We brought the example of the space under the Viaduct of Madureira in Rio de Janeiro, which had not only its image of passage place transformed, as its significance to become a place of meeting of the public life through the performances of the "Cultural Space Rio Hip-Hop Charme" and" CUFA Madureira". Our theoretical construct was based on research and searching at official websites of CUFA Movement and the Hip-Hop and also on theoretical arguments of hybrid cultures, cultural action and public space by some authors.